Behavioural response patterns: an investigation of the early stages of major incidents. Issue 4 (13th August 2018) - Hanna Sawalha, Ihab
Abstract : Purpose: This paper aims to investigate the different patterns of organizational behavioural responses to major incidents and develop an original classification of these patterns. Design/methodology/approach: An extensive literature review was made to investigate the different patterns of behavioural responses to major incidents and then to develop an original classification of these patterns. Several sources of information, such as case studies, technical reports, academic journal articles and organizational internal reports were used. Findings: Organizations respond differently to major incidents. This was clear from the different behavioural patterns investigated and identified. Behavioural patterns determine levels of resilience and ability of organizations to overcome and ultimately survive major incidents. Practical implications: To promote effective and organized behavioural response patterns to major incidents and improve consistency of responses across the organization, relevant authorities should demonstrate to all private and public enterprises the significance of effective behavioural responses, thus enabling them to better respond to various potential emergencies. Originality/value: A number of models of human behaviour have been introduced in the literature to understand how people respond to emergency situations. They each take a different perspective on human behaviour but no single theory has emerged as the leading paradigm. This highlights the complexity of understanding human behaviour in such situations and the need for a better classification of behavioural patterns. To the author's knowledge, this is one of very few studies to investigate, identify and categorize behavioural response patterns to major incidents. This research is expected to be of a substantial value for those interested in improving organizational behaviour during major incidents, as well as those interested in improving organizational resilience.